2013
DOI: 10.1159/000342301
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Mammalian Hepatitis E Virus Infection

Abstract: Mammalian hepatitis E virus (HEV), the etiological agent of hepatitis E in humans, is a recently discovered infectious agent. It was identified for the first time in 1983 using electron microscopy on a faecal specimen of a person infected with non-A, non-B enterically-transmitted hepatitis. Based on retrospective and prospective studies, HEV was long described as one of the leading causes of acute viral hepatitis in tropical and subtropical countries, whereas in developed countries hepatitis E was considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 296 publications
(489 reference statements)
0
30
0
1
Order By: Relevance
“…Genotypes 1 and 2 infect humans and nonhuman primates exclusively, whereas genotype 3 and 4 viruses are enzootic, ubiquitous in swine, and present to a lesser extent in other human food sources, such as deer, rabbits, and cows (6,7). Genotype 1 commonly causes sporadic cases and epidemic waterborne acute hepatitis in developing countries with inadequate sanitation.…”
mentioning
confidence: 99%
“…Genotypes 1 and 2 infect humans and nonhuman primates exclusively, whereas genotype 3 and 4 viruses are enzootic, ubiquitous in swine, and present to a lesser extent in other human food sources, such as deer, rabbits, and cows (6,7). Genotype 1 commonly causes sporadic cases and epidemic waterborne acute hepatitis in developing countries with inadequate sanitation.…”
mentioning
confidence: 99%
“…Nowadays, hepatitis E is common not just in developing countries with inadequate water supply and environmental sanitation, but more autochthonous sporadic cases are diagnosed also in industrialized countries (Mansuy et al 2008;Kaba et al 2013), possibly mediated by the international trade of pigs, migration of wild animals, human contact with animals and their biological material, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study from the UK indicated that 92.8% of 640 pigs sampled at slaughter were seropositive to HEV (Tedder 2014). Approximately 62% and 73% of serum from domestic pigs were positive for anti-HEV IgG antibodies in Estonia (Ivanova et al 2015) and Denmark (Kaba et al 2013), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations